2019
DOI: 10.1055/a-1005-8678
|View full text |Cite
|
Sign up to set email alerts
|

Körperliches Training bei pulmonaler Hypertonie – ein systematisches Review mit Metaanalyse

Abstract: Zusammenfassung Hintergrund Pulmonale Hypertonie (PH) ist definiert als ein Anstieg des mittleren pulmonal-arteriellen Drucks auf > 20 mmHg in Ruhe, der auf Dauer zu einer Rechtsherzinsuffizienz führen kann. Bis vor einigen Jahren wurde PH-Patienten wegen der Befürchtung einer möglichen Symptomverschlechterung und dem Auftreten unerwünschter, belastungsassoziierter klinischer Ereignisse von körperlichem Training abgeraten. Methoden Drei elektronische Datenbanken wurden mit folgenden Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The effectiveness of the program is comparable or greater than that reported in previously published interventions based mainly on closely supervised rehabilitation in medical facilities. The impact of physical training on functional parameters has been revealed in meta-analyses [ 12 , 25 , 26 ] which demonstrated, inter alia, improvements in 6MWT (6MWD) by 53–72 m, peak VO 2 /kg in the range of 1.5–2.2 ml/min/kg, and workload by 14.9 W [ 9 ]. Our study, compared with these analyses, showed an improvement in 6MWD by 71.4 m after the intervention period, revealing equally high effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the program is comparable or greater than that reported in previously published interventions based mainly on closely supervised rehabilitation in medical facilities. The impact of physical training on functional parameters has been revealed in meta-analyses [ 12 , 25 , 26 ] which demonstrated, inter alia, improvements in 6MWT (6MWD) by 53–72 m, peak VO 2 /kg in the range of 1.5–2.2 ml/min/kg, and workload by 14.9 W [ 9 ]. Our study, compared with these analyses, showed an improvement in 6MWD by 71.4 m after the intervention period, revealing equally high effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Despite of severe symptoms and limitations in exercise capacity, until recently physical activity including exercise training has often been discourgaed in patients with pulmonary artery hypertension, particularly in those with more advanced disease due to safety concerns. 96 In the meantime, however, exercise training has been shown to be safe and efficacious in these patients, 97 and international guidelines recommend its use in experienced centers for patients who are clinically stable and on optimal pharmacological treatment. 96 It has further been observed that after successful pulmonary endarterectomy surgery, patients can still have limited exercise capacity, 98 especially if pulmonary hemodynamics do not completely normalize.…”
Section: Rehabilitation For Patients With Chronic Thromboembolic Pulm...mentioning
confidence: 99%